1985
DOI: 10.2527/jas1985.6061385x
|View full text |Cite
|
Sign up to set email alerts
|

Selection for Increased Weaning or Yearling Weight in Hereford Cattle. II. Direct and Correlated Responses2

Abstract: Selection was applied from 1964 to 1978 for increased weaning weight (WWL) or yearling weight (YWL) in two Hereford lines. An Angus line was maintained as an unselected control line (CL). Each line was maintained with 50 cows and four sires each year (two sires selected each year and used for 2 yr). Primary traits measured in the lines were birth weight (BW), preweaning daily gain (WDG), weaning weight (WW), weaning conformation grade (WG), weaning condition score (WC), weaning to yearling daily gain (YDG), ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1987
1987
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 14 publications
(19 reference statements)
0
4
0
Order By: Relevance
“…Hough et al (1985) determined that correlated response and genetic trend for WWT in response to sire selection based upon yearling weight EPDs were 15 -+ 2 kg (P<.01) and 4.6 -+ .7 kg (P<.O1), respectively. Selection for yearling weight increased ADG and WWT, 3.61 + 1.44g'd -1 "yr -1 (P<.01) and 1.00 -+ .31 kg'yr -1 (P<.01), respectively (Frahm et al, 1985).…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…Hough et al (1985) determined that correlated response and genetic trend for WWT in response to sire selection based upon yearling weight EPDs were 15 -+ 2 kg (P<.01) and 4.6 -+ .7 kg (P<.O1), respectively. Selection for yearling weight increased ADG and WWT, 3.61 + 1.44g'd -1 "yr -1 (P<.01) and 1.00 -+ .31 kg'yr -1 (P<.01), respectively (Frahm et al, 1985).…”
Section: Resultsmentioning
confidence: 92%
“…Hough et al (1985) found that BWT was increased 1.4 kg (P<.01) in response to openqine selection that used Hereford sires ranked on the basis of their progeny yearling weight performance. Frahm et al (1985) determined that BWT increased .26 kg'yr -1 (P< .01) in response to yearling weight selection. Koch et al (1982a) reported that selection for increased yearling weight and on an index of yearling weight and muscling score increased CD in 2-yr-old, first-calf heifers, Also, selection for weight in all selection lines resulted in increased calf mortality compared with the control line.…”
Section: Resultsmentioning
confidence: 96%
“…Next, we sought to identify which of the correlations among the growth performance traits examined above offer the best selection option in Nilotic cattle, because selections based on growth traits sometimes yield undesirable outcomes. One of such undesirable outcomes is increased incidences of dystocia caused by increased birth weight, which often leads to the calf`s and/or mother`s death [32] and [33]. Indeed, dystocia is not uncommon in Nilotic cattle, although its rate of occurrence and causes remained uninvestigated [34].…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, the selection of cows and heifers in respect of the uterine composition is crucial in achieving breeding herds with appropriate productivity, exterior and constitutional features, milk-producing ability, reproductive ability, good maternal qualities, health, and uniformity. All of these factors rely on the provenance of the cattle; according to those in the field, they must be from outstanding proven bulls [ 15 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%